Exploring the Socio-Semantic and Communicative Dimensions of Idiomatic Expressions in Ibibio (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
Language serves not only as a medium of communication but also as a repository of cultural knowledge and social experience. Idiomatic expressions, as fixed or semi-fixed linguistic units, encapsulate a community’s worldview, values, and modes of interaction. This study explores the socio-semantic and communicative dimensions of idiomatic expressions in Ibibio, a Lower Cross language spoken predominantly in Akwa Ibom State, Nigeria. The research examines how Ibibio idioms reflect social realities, encode cultural meanings, and perform pragmatic functions within diverse communicative contexts. Drawing from sociolinguistic, semantic, and pragmatic frameworks, the study employs both qualitative and descriptive approaches, relying on oral interviews, native speaker intuitions, and textual sources for data collection. The data recorded were analyzed using the contextual theory. The analysis focuses on the relationship between idiomatic meaning and socio-cultural context, highlighting how figurative language serves as a communicative strategy for expressing emotions, moral values, and social hierarchies. Findings reveal that Ibibio idioms are deeply embedded in communal experiences and social cognition, functioning not only as linguistic artifacts but also as vehicles of social cohesion and moral instruction. By highlighting the interplay between form, meaning, and social use, this study contributes to a broader understanding of how language reflects and shapes cultural identity in African linguistic communities. The work recommends a documentation and preservation of Ibibio idioms, while contributing to the theoretical insight in the language, as well as the Ibibio socio- cultural knowledge and its conservation.